REFUGEE INFLUX AND ITS IMPACT ON ECONOMIC GROWTH IN KENYA - Wahogo, George Macharia; Ruigu, Dr. George (International Journal of Economics, 2016)
Purpose: The general objective of this study was to establish the impact of refugee influx on economic growth in Kenya. Methodology: The study adopted a time series methodology. Findings: The results indicated that there was at least one co-integrating equation in the long run. It results also indicated that the lag GDP (denoting the previous period GDP) affects the current period GDP positively. This implies a higher GDP in the previous period leads to an increase in the current period GDP. Results also indicated that both in the long run and short run the number of refugees had a negative and significant relationship with GDP. Hence, an increase in the number of refugees resulted to a decrease in GDP. The results indicated that both in the long run and short run, labour had a positive and significant relationship with the GDP. Therefore, an increase in labour resulted to an increase in GDP. The other variables were insignificant both in the short run and long run which implies that change in capital and human capital will have no effect on GDP in the shortrun and longrun that could be due to the impact of inflation. Unique contribution to theory, practice and policy: This study can be a source of solution to be implemented by government and non-governmental policy makers as it outlined the impact of refugees influx to economic growth so as to see how curbing any refugee crisis would affect the economic outlook. In addition, the study recommendations in the wake of the refugee situation in Kenya as with regard to the economic situation would be vital for achieving such ends as those envisaged in the vision 2030. The aftereffects of the study would also contribute towards filling the data crevice on the topic. It is trusted that the discoveries of the study will make significant augmentations to the writing in the field of refugee influx and economic growth fortifying further interest.